Identity and Reproductive Aspects in Females with Fragile X Syndrome - Sarah Reiss; Laura Zalles; Catherine Gbekie; Reymundo Lozano (Women's Health Reports, 2021)
Purpose: Fragile X Syndrome (FXS) is caused by a full mutation in the FMR1 gene, defined by >200 CGG repeats. It is the leading cause of inherited intellectual disability, but presents with a wide range of clinical variability in males and particularly amongst females. This article aims to review the perspectives of women with the full mutation in relation to Fragile X Syndrome identification, romantic desires, and reproductive decision making. Methods: We generated an online survey of 33 questions to be administered to 31 women that had visited our Fragile X Syndrome Clinic and members of the National Fragile X Foundation. We extrapolated common themes from the obtained data. Results: The results showed that most women often struggled with identifying as a female with FXS. Furthermore, many women are interested in childbearing, however most are in need of genetic counseling. Conclusions: Further research to advance the understanding of the specific needs of women with FXS is necessary.